1980
DOI: 10.1007/bf00439481
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical relationships in 31 human pituitary adenomas with acromegaly

Abstract: In 22 pure GH cell adenomas and 9 mixed GH cell-prolactin cell adenomas with acromegaly, we compare the morphological and functional data (secretory activity and granular appearance) with GH levels (radioimmunoassays) in the blood and in the tumor. According to morphological criteria, the secretory activity is marked in 13 cases (Group I), mild in 9 cases (Group II), and weak in 9 others (Group III). The mean values of the plasma GH levels in the 3 groups (80 ng/ml plus or minus 22; 26.5 ng/ml plus or minus 2;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In our study we found no relation be¬ tween the percentages of GH-and PRL-cells as de¬ tected by immunocytochemistry and the plasma GH and PRL values, respectively. This discrepancy between immunocytochemical data and plasma GH and PRL levels is in agreement with earlier findings by others (12,25). Data with respect to the frequency of mammosomatotropic cells within pi¬ tuitary adenomas from acromegalic patients are conflicting so far.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In our study we found no relation be¬ tween the percentages of GH-and PRL-cells as de¬ tected by immunocytochemistry and the plasma GH and PRL values, respectively. This discrepancy between immunocytochemical data and plasma GH and PRL levels is in agreement with earlier findings by others (12,25). Data with respect to the frequency of mammosomatotropic cells within pi¬ tuitary adenomas from acromegalic patients are conflicting so far.…”
Section: Resultssupporting
confidence: 83%
“…This has been demonstrated by several in vitro studies (1)(2)(3)(4)(5)(6) and by morphological techniques (1,(7)(8)(9)(10)(11)(12)(13). However, pituitary adenomas from acro¬ megalic patients are very heterogeneous with re¬ spect to their cellular composition.…”
mentioning
confidence: 87%
“…suggested that GH and Prl are secreted both by different cells (Corenblum et al 1976) and by the same cells (Trouillas et al 1980) without any corre¬ lation to Prl basal levels.…”
Section: Discussionmentioning
confidence: 98%
“…In case of acromegaly, some authors [19] described an inverse correlation of se rum GH levels to granularity ('well' or 'poorly granulated'), whereas others [17,31] could not find such a clear inverse correlation to the granules. (Ultra-)structural signs of ac tivity on the other hand appeared to correlate to serum GH levels [22,31], It might be that these discrepancies are due to the existence of 2 ultrastructurally distinct tumor types exist ing with an equal incidence [15], the densely and the sparsely granulated GH cell adeno mas [16]. Prolactinoma cells, in contrast to GH-producing tumor cells, are almost always sparsely granulated.…”
Section: Discussionmentioning
confidence: 99%